KAJIAN CAHAYA PERSPEKTIF FISIKA DAN TASAWUF - Mulyono, Agus (ULUL ALBAB Jurnal Studi Islam, 2008)
Light plays vital role in human life, without which objects will be impossible to see and the beauty of world and universe will not be unseen. The theory of light merely describes its nature and leaves the essence unknown. Samuel Johnson maintains that light is known to everybody, but it is not easy to reveal its reality.Light of universe is the light of God shining upon the heart of His open-hearted servants dan embellishing His pious and devoted ones. Therefore, the heart of servant who is endowed with God's light will glow like the sun shining the moon. God's light in human heart surpasses fender light of the moon, becomes cure and draw near to God.